A distant soil (1991), volume 1 ebook The gathering. - Doran, Colleen (A Distant Soil (1991), 2013)
Collects A Distant Soil 1-7! The first new edition of the out of print A DISTANT SOIL, VOL. 1 collection returns in a spectacular, digitally re-mastered volume! This beautiful and critically acclaimed series has not had a new edition in seventeen years. Now, digital technology allows us to bring you a more beautiful presentation than ever before. Every single page has been completely restored, and re-lettered, with a new and stunning die cut cover! This is THE DEFINITIVE VERSION fans have been waiting for!. Author: Colleen Doran. Illustrator: Colleen Doran . 2013 Colleen Doran.